Answer:
the answer is d. 4x²+x-6
Explanation:
In order to combine the fractions, they need to have the same denominator.
So, multiply each of their numerators by the denominator they need to be equivalent.
This would look like this:
3x/x+3 --> 3x(x)/x(x+3) ---simplify this as--> 3x²/x(x+3)
x-2/x --> (x-2)(x+3)/x(x+3) ---simplify this as --> x²+x - 6/x(x+3)
3x 3x(x) x-2 (x-2)(x+3)
----- ---> ----- and -------- ---> ---------
x+3 x(x+3) x x(x+3)
now that both fractions have the same denominator, we can add their numerators.
3x² + x²+x-6 = 4x²+x -6
This should now look like this:
4x²+x -6
-------------
x(x+3)